دور القيادة التحويلية في تحسين المها ا رت لدى الموارد البشرية)د ا رسة حالة: بلدية المقرن – الوادي( - انور, بن عمر; محمد الصالح, بن ساسي; يوسف, كحلاوي (University of eloued جامعة الوادي, 2020)
"ملخص الدراسة: هدفت الدراسة الى التعرف على دور القيادة التحويلية في تحسين المهارات لدى الموارد البشرية، دراسة حالة بلدية المقرن، الوادي. وتم استخدام الاستبانة كأداة لجمع البيانات، حيث قسمت الى ثلاثة محاور، تمثل المحور الأول في الخصائص الشخصية والوظيفية لعينة الدراسة، والتي تكونت من 55 مفردة، أما المحور الثاني وهو المتغير المستقل في الدراسة تمثل في أبعاد القيادة التحويلية وهي أربعة )التأثير المثالي، التحفيز الالهامي، الاستشارة الفكرية والاعتبار الفردي(، والمحور الأخير وهو المتغير التاب ع، والمتمثل في تحسين المهارات، قسم الى ثلاثة أبعاد )المهارات الفردية، ،)spss( المهارات الجماعية، المهارات التنظيمية(. ولتحليل البيانات تم استخدام الرزمة الإحصائية للعلوم الاجتماعية الإصدار رقم 25 . توصل الطلبة في الأخير الى مجموعة من النتائج أهمها يوجد تأثير معنوي ذو دلالة إحصائية لنمط القيادة التحويلية في تحسين مهارات الموارد البشرية في بلدية المقر ن، الوادي. كما أوصت الدراسة بضرورة تنمية وتطوير نمط القيادة التحويلية في المؤسسة كون له علاقة تأثير إيجابية قوية مع الموارد البشرية. ""The study aimed to identify the role of transformational leadership in improving the competences of human resources, a case study of El magrane municipality, El oued. The questionnaire was used as a tool to collect data, Where it was divided into three axes, the first axis represented in the personal and functional characteristics of the study sample, Which consisted of 55 individuals, The second axis, which is the independent variable in the study, is represented in the transformational leadership dimensions, which are four (Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration), the last axis which is the dependent variable, which is represented in competencies development, is divided into three dimensions (individual competences, collective competences andorganizational competences). To analyze the data we used statistical package for Social Sciences (SPSS), version number (25). Finally, the students reached a set of results, the most important of which is a statistically significant impact of the transformational leadership pattern on improving human resource competences in the El magrane municipality, El oued. The study also recommended the need to develop and develop the transformational leadership style in the organization as it has a strong positive impact relationship with human resource competences. "
مذكرة ماستر ادارة اعمال
Keywords: القيادة التحويلية، تحسين مهارات، الاستشارة الفكرية، المهارات التنظيمية; transformational leadership, Improving of competences, organizational competences, intellectual stimulation.